Assembly Transformation Jointly Driven by the LAP Enzyme and GSH Boosting Theranostic Capability for Effective Tumor Therapy - Wang, Anna; Fang, Jing; Ye, Shuyue; Mao, Qiulian; Zhao, Yan; Cui, Chaoxiang; Zhang, Yuqi; Feng, Yali; Li, Jiachen; He, Lei; Qiu, Ling; Shi, Haibin (ACS applied materials & interfaces, 2021)
Developing intelligent and morphology-transformable nanomaterials that can spatiotemporally undergo stimulus-responsive size transformation holds great promise for improving the tumor delivery efficiency of drugs . Here, we report a smart size-transformable theranostic probe Ce6-Leu consisting of a leucine amino peptidase (LAP) and glutathione (GSH) dual-responsive moiety, an 1,2-aminothiol group, and a clinically used photosensitizer Ce6. This probe tends to self-assemble into uniform nanoparticles with an initial size of ∼80 nm in aqueous solution owing to the amphiphilic feature. Surprisingly, taking advantage of the biocompatible CBT-Cys condensation reaction, the large nanoprobes can be transformed into tiny nanoparticles (∼23 nm) under the joint action of LAP and GSH in a tumor microenvironment, endowing them with great tumor accumulation and deep tissue penetration. Concomitantly, this LAP/GSH-driven disassembly and size shrinkage of Ce6-Leu can also activate the fluorescence/magnetic resonance signals and the photodynamic effect for enhanced multimodal imaging-guided photodynamic therapy of human liver HepG2 tumors . More excitingly, the Mn -chelating probe (Ce6-Leu@Mn ) was demonstrated to have the capability to catalyze endogenous H O to persistently release O at the hypoxic tumor site, as a consequence improving the oxygen supply to boost the radiotherapy effect. We thus believe that this LAP/GSH-driven size-transformable nanosystem would offer a novel advanced technology to improve the drug delivery efficiency for achieving precise tumor diagnosis and treatment.